Interactive effects of AM251 and baclofen on synaptic plasticity in the rat dentate gyrus - Nazari, Masoumeh; Komaki, Alireza; Salehi, Iraj; Sarihi, Abdolrahman; Shahidi, Siamak; Komaki, Hamidreza; Ganji, Ahmad (Brain research, 2016)
Long-term potentiation (LTP), a form of synaptic plasticity, is considered to be a critical cellular mechanism that underlies learning and memory. Cannabinoid CB1 and metabotropic GABAB receptors display similar pharmacological effects and co-localize in certain brain regions. In this study, we examined the effects of co-administration of the CB1 and GABAB antagonists AM251 and baclofen, respectively, on LTP induction in the rat dentate gyrus (DG). Male Wistar rats were anesthetized with urethane. A stimulating electrode was placed in the lateral perforant path (PP), and a bipolar recording electrode was inserted into the DG until maximal field excitatory postsynaptic potentials (fEPSPs) were observed. LTP was induced in the hippocampal area by high-frequency stimulation (HFS) of the PP. fEPSPs and population spikes (PS) were recorded at 5, 30, and 60min after HFS in order to measure changes in the synaptic responses of DG neurons. Our results showed that HFS coupled with administration of AM251 and baclofen increased both PS amplitude and fEPSP slope. Furthermore, co-administration of AM251 and baclofen elicited greater increases in PS amplitude and fEPSP slope. The results of the present study suggest that CB1 receptor activation in the hippocampus mainly modifies synapses onto GABAergic interneurons located in the DG. Our results further suggest that, when AM251 and baclofen are administered simultaneously, AM251 can alter GABA release and thereby augment LTP through GABAB receptors. These results suggest that functional crosstalk between cannabinoid and GABA receptors regulates hippocampal synaptic plasticity. •Cannabinoid receptors (CB1) participate in multiple type of synaptic plasticity.•CB1 receptor stimulation affects the release of GABA.•GABAB receptors play a substantial role in long-term potentiation (LTP).•CB1 antagonists can alter GABA release, which in turn enhances LTP.•GABAB and CB1 receptors may have a functional interaction in signaling pathway in LTP.